Nicotinamide Riboside Neutralizes Hypothalamic Inflammation and Increases Weight Loss Without Altering Muscle Mass in Obese Rats Under Calorie Restriction: A Preliminary Investigation - de Castro, Josimar Macedo; Stein, Dirson João; Medeiros, Helouise Richardt; de Oliveira, Carla; Torres, Iraci L. S. (Frontiers in Nutrition, 2021)
Obesity treatments, such as calorie restriction (CR), eventually lead to muscle wasting and higher rates of neuroinflammation, while hypothalamic inflammatory conditions impair body weight control. Nicotinamide riboside (NR) has been proposed against obesity but with little evidence on skeletal muscle tissue (SMT) and neuroinflammation. Therefore, we aimed to investigate the effects of CR on SMT as well as on hypothalamic inflammatory biomarkers in obese adult male Wistar rats, and whether NR supplementation alone or combined with CR affects these parameters. Obesity was induced in rats through a cafeteria diet for 6 weeks. After that, a group of obese rats was exposed to CR, associated or not with NR supplementation (400 mg/kg), for another 4 weeks. As a result, obese rats, with or without CR, presented lower relative weight of SMT when compared to eutrophic rats. Rats under CR presented lower absolute SMT weight compared to obese and eutrophic rats, in addition to presenting elevated hypothalamic levels of TNF-α. NR supplementation, in all groups, enhanced weight loss and increased relative weight of the SMT. Furthermore, in animals under CR, NR reversed increases in TNF-α levels in the hypothalamus. In the literature, these data, although succinct, are the first to evidence the effects of NR on SMT and neuroinflammation when associated with CR, especially in obesity conditions. Therefore, this provides preliminary support for future studies in this investigative field. Furthermore, NR emerges as a potential adjuvant for preventing muscle mass loss in weight loss processes.